2008
DOI: 10.1182/blood-2008-01-134056
|View full text |Cite
|
Sign up to set email alerts
|

The PHD fingers of MLL block MLL fusion protein–mediated transformation

Abstract: IntroductionBalanced translocations involving mixed lineage leukemia (MLL) are common in human acute myeloid leukemia (AML) and acute lymphoid leukemia (ALL). 1 MLL positively regulates Hox and other target gene expression through SET domaindependent histone H3 lysine 4 methyltransferase activity. 2,3 Like MLL, MLL fusion proteins bind directly to Hox loci and up-regulate their expression. 2-5 Deregulated expression of Hox genes including Hoxa9 and the Hox cofactor Meis1 appears to be central for MLL fusion pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 23 publications
2
38
0
Order By: Relevance
“…68,69 In addition, it was mandatory that the breakpoint in MLL was upstream of the PHD fingers because artificial MLL fusions including this domain lost their transforming capacity. 70,71 This explains the strict conservation of the fusion breakpoints found in leukemic blasts. Further studies suggested that the leukemogenic potential of truncated MLL could be activated in at least four different ways (Figure 3).…”
Section: Mll Fusion Proteins; Transcriptional Elongation and Chromatimentioning
confidence: 99%
“…68,69 In addition, it was mandatory that the breakpoint in MLL was upstream of the PHD fingers because artificial MLL fusions including this domain lost their transforming capacity. 70,71 This explains the strict conservation of the fusion breakpoints found in leukemic blasts. Further studies suggested that the leukemogenic potential of truncated MLL could be activated in at least four different ways (Figure 3).…”
Section: Mll Fusion Proteins; Transcriptional Elongation and Chromatimentioning
confidence: 99%
“…In particular, the third PHD finger (PHD3) was shown to associate with di-or tri-methylated histone H3 lysine 4, which might be regulated by Cyp33 binding (Fair et al, 2001;Chang et al, 2010;Milne et al, 2010;Wang et al, 2010b). PHD3 is not present in the leukemic MLL fusion proteins and diminishes oncogenic ability if artificially included in an MLL fusion protein (Muntean et al, 2008;Chen et al, 2008). MLL N associates with menin and LEDGF, which are also crucial for linking MLL proteins with target chromatin (Yokoyama and Cleary, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The MLL gene encodes a 430-kDa protein containing three AT hook motifs, two speckled nuclear localization domains (SNL1 and SNL2), a CXXC zinc finger motif, multiple plant homology domains (PHDs), 2 and a Su/var, Enhancer or zeste, Trithorax (SET), domain. The PHD fingers contribute to protein-protein interactions, and their deletion, as a result of chromosomal translocation, is necessary for MLL fusion proteins to induce hematopoietic cell immortalization (9). The SET domain contributes to modulation of homeobox (HOX) gene expression by facilitating histone H3 Lys-4 methylation at the proximal promoter region (10).…”
mentioning
confidence: 99%